Amenities and Rural Development 2005
DOI: 10.4337/9781845428075.00009
|View full text |Cite
|
Sign up to set email alerts
|

The Supply of Natural Amenities: Moving from Empirical Anecdotes to a Theoretical Basis

Abstract: Although a significant amount of empirical research makes linkages between natural amenities and developmental attributes within the context of rural change, there has yet to be forwarded a defensible, comprehensive, and explanatory theoretical construct upon which to better understand the presence, use, and production of natural amenities within the context of development. Key unique attributes of natural amenity resources identify short-term issues of irreversibility, non-producibility, and nontradability. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…Both descriptive analysis (e.g., McGranahan 1999) and more advanced statistical modeling approaches (e.g., Deller et al 2001, Marcouiller, Kim, and Deller 2004 have consistently found that rural areas that are endowed with natural and built amenities such as scenic beauty, wildlife, and recreational and tourism attributes experience higher rates of structural change and economic growth than the U.S. average. Unfortunately, much of the current thinking is based on empirical evidence with little if any theoretical foundations (Power 1996(Power , 2005.Using traditional neoclassical growth theory, Marcouiller (1998) and Marcouiller and Clendenning (2005) suggest that natural amenities and quality of life factors act as non-market latent inputs into regional economic growth and development. As our national economy has moved from goods-to service-producing, the impact on rural America has been pronounced.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Both descriptive analysis (e.g., McGranahan 1999) and more advanced statistical modeling approaches (e.g., Deller et al 2001, Marcouiller, Kim, and Deller 2004 have consistently found that rural areas that are endowed with natural and built amenities such as scenic beauty, wildlife, and recreational and tourism attributes experience higher rates of structural change and economic growth than the U.S. average. Unfortunately, much of the current thinking is based on empirical evidence with little if any theoretical foundations (Power 1996(Power , 2005.Using traditional neoclassical growth theory, Marcouiller (1998) and Marcouiller and Clendenning (2005) suggest that natural amenities and quality of life factors act as non-market latent inputs into regional economic growth and development. As our national economy has moved from goods-to service-producing, the impact on rural America has been pronounced.…”
mentioning
confidence: 99%
“…Using traditional neoclassical growth theory, Marcouiller (1998) and Marcouiller and Clendenning (2005) suggest that natural amenities and quality of life factors act as non-market latent inputs into regional economic growth and development. As our national economy has moved from goods-to service-producing, the impact on rural America has been pronounced.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Deller et al, 2001;Gottlieb, 1995;Green, 2001;Marcouiller and Clendenning, 2005) we define natural landscape amenities as landscape features that are location-specific, latent non-market input goods of an economy that directly enter a resident's utility function or attract firms in amenity-related industries. Based on the results, we discuss main insights but also remark on limitations of the literature as a basis for public decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these advantages are not limited to the criteria of proximity to one's place of work or accessibility in general. A number of authors have shown that certain, mostly rural regions experienced a population influx motivated above all by the quality of the landscape and environment, the possibilities of outdoor leisure activities, or generally a better quality of life (Benson, O'Reilly 2009;Marcouiller, Clendenning 2005). With regard to mountainous regions, scholars speak of so-called amenity migration to describe the new migrants who are interested in the tourist and landscape features of the places where they settle (Martin, Bourdeau, Daller 2012;Moss et al 2009).…”
mentioning
confidence: 99%